2008
DOI: 10.1097/brs.0b013e318178e624
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Clinical Presentation of Idiophatic Thoracic Spinal Cord Herniation

Abstract: Idiopathic spinal cord herniation is 1 of the causes of unexplained atypical thoracic pain with or without signs and symptoms of myelopathy. Magnetic resonance imaging is recommended to establish the diagnosis in patients, particularly age ranged from 36 to 59, whose clinical and laboratory findings are inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Due to its rarity and atypical presentation, ISCH is a difficult clinical diagnosis and patients like those in this case series may experience a delay in diagnosis and treatment. 8, 9, 13, 14, 16, 17, 21 Although the etiology underlying ISCH has remained disputed, this series and prior reports 16, 33 continue to suggest that a trauma is a likely proximate cause of ISCH. Four patients in this series experienced severe traumatic injuries, one with a vertebral fracture at the level of ISCH and another with a nerve root avulsion injury.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Due to its rarity and atypical presentation, ISCH is a difficult clinical diagnosis and patients like those in this case series may experience a delay in diagnosis and treatment. 8, 9, 13, 14, 16, 17, 21 Although the etiology underlying ISCH has remained disputed, this series and prior reports 16, 33 continue to suggest that a trauma is a likely proximate cause of ISCH. Four patients in this series experienced severe traumatic injuries, one with a vertebral fracture at the level of ISCH and another with a nerve root avulsion injury.…”
Section: Discussionmentioning
confidence: 73%
“…1820 The chronic atypical presentation and diagnostic challenge often leads to a delay in diagnosis and treatment. 8, 9, 13, 14, 16, 17, 21 There is little consensus on the management for asymptomatic ISCH 17 . However, the literature anecdotally supports surgical intervention in patients with ISCH and myelopathy symptoms that are not attributable to another cause.…”
mentioning
confidence: 99%
“…It has been shown the TSCH patients were initially asymptomatic [8]. In addition, these symptoms typically are long lasting before the precise diagnosis [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…1,2,17,23,37 In one of the largest series, Massicotte et al 23 reported on 8 patients, 4 of whom did not have surgery. These 4 patients were observed for up to 8 years after presentation and none developed progressive neurological symptoms.…”
Section: Surgery and Techniquesmentioning
confidence: 99%
“…Similarly, Ammar et al 2 reported on 2 patients who presented without weakness or spasticity and were followed for 15 months in one and 5 years in the other, without progression of symptoms. Senturk et al 37 followed a 38-year-old woman with progressive thoracic back pain without neurological deficits for 6 months without progression of symptoms. Hausmann and Moseley 17 reported on 2 patients who presented with spasticity and weakness, but did not undergo surgery.…”
Section: Surgery and Techniquesmentioning
confidence: 99%